USE OF HAND GESTURES THROUGH DIGITAL VIDEO TO IMPROVE PHONEMIC AWARENESS AMONG YEAR 2 PUPILS - Bee Choo Yee; Nursasniza Adilah Abd. Samad (Universitas Sembilanbelas November Kolaka, 2019)
Pupils need phonemic awareness so that they have the ability to manipulate the individual sounds in words. However, they sometimes focused more on reading comprehension rather than recognizing the letter sounds which build the words for reading. This action research was designed to improve the pupils’ phonemic awareness by using hand gestures through digital video and it involved three cycles. The participants involved were 24 Year 2 pupils from one of the primary schools in Malaysia. Three different data collection methods used were tests, pupils’ work and observation. The findings showed there was an improvement of mean scores from 40% in Test 1 to 91% in Test 2. The pupils’ oral exercises also improved from 52.14% to 96.07%. The results from the observation checklist and notes also showed they became more aware in learning English through their increased communication and active participation in the lesson. This shows that the technique was able to help pupils to learn and remember the sounds of phonemes as they could read the words correctly. It is suggested to carry out further research to develop the pupils’ skills in phonemic awareness through body movements in addition to hand gestures.